Concurrent Massive Pulmonary Embolism With Emboli in Transit and Anterior ST Elevation Myocardial Infarction with Increased Bleeding Risk Successfully Treated with Low-Dose Systemic Alteplase: A Case Report - Seguban, Joseph Marc S.; Alajar, Elaine; Isidro, Jessore; Pestaño, Noemi; Punzalan, Felix Eduardo; Castillo, Rafael R. (Cardiology and Cardiovascular Medicine, 2019)
Massive pulmonary embolism (MPE) and acute myocardial infarction (AMI) are both life-threatening conditions, and the concomitant presence of both, though a rare occurrence, usually ends in a fatal outcome. A 67-year-old male, hypertensive, smoker with recent surgery for prostate cancer presented with dyspnea, syncope and angina. His electrocardiogram revealed anterior wall STEMI; echocardiogram showed left ventricular segmental hypokinesia, with right atrial thrombus—likely an embolus in transit—and right ventricular dysfunction. Compression ultrasound revealed a left popliteal vein thrombosis. Coronary angiography showed left main coronary and left anterior descending artery stenoses for which angioplasty with stenting was performed. Pulmonary angiography showed filling defects in the main pulmonary arteries consistent with massive pulmonary embolism. Computed tomography pulmonary angiography showed another likely embolus in transit at the superior vena cava. Despite the coronary intervention, his dyspnea persisted even at rest, thus intravenous tissue plasminogen activator (tPA) was administered at a reduced dose (50 mg for 2 hours) due to high risk of bleeding. He improved dramatically after the thrombolytic infusion and was discharged improved on the 9th hospital day, and improved further clinically and by echocardiogram on 3-month follow up. To our knowledge, this is the first reported case showing the efficacy and safety of low-dose alteplase in massive pulmonary embolism with documented emboli in transit at the superior vena cava and right atrium, in a setting of an acute anterior wall STEMI, who had just undergone PCI. This is also the first reported case in our country to manage such a complicated case of MPE with low-dose alteplase (50 mg) leading to a favorable&